Complement Activation Profile in Myasthenia Gravis Patients: Perspectives for Tailoring Anti-Complement Therapy - Nicola Iacomino; Fiammetta Vanoli; Rita Frangiamore; Marta Ballardini; Letizia Scandiffio; Federica Bortone; Francesca Andreetta; Fulvio Baggi; Pia Bernasconi; Carlo Antozzi; Paola Cavalcante; Renato Mantegazza (Biomedicines, 2022)
The complement system plays a key role in myasthenia gravis (MG). Anti-complement drugs are emerging as effective therapies to treat anti-acetylcholine receptor (AChR) antibody-positive MG patients, though their usage is still limited by the high costs. Here, we searched for plasma complement proteins as indicators of complement activation status in AChR-MG patients, and potential biomarkers for tailoring anti-complement therapy in MG. Plasma was collected from AChR-MG and MuSK-MG patients, and healthy controls. Multiplex immunoassays and ELISA were used to quantify a panel of complement components (C1Q, C2, C3, C4, C5, Factor B, Factor H, MBL, and properdin) and activation products (C4b, C3b, C5a, and C5b-9), of classical, alternative and lectin pathways. C2 and C5 levels were significantly reduced, and C3, C3b, and C5a increased, in plasma of AChR-MG, but not MuSK-MG, patients compared to controls. This protein profile was indicative of complement activation. We obtained sensitivity and specificity performance results suggesting plasma C2, C3, C3b, and C5 as biomarkers for AChR-MG. Our findings reveal a plasma complement “C2, C3, C5, C3b, and C5a” profile associated with AChR-MG to be further investigated as a biomarker of complement activation status in AChR-MG patients, opening new perspectives for tailoring of anti-complement therapies to improve the disease treatment.